Ultrasound-Guided Insertion of the Ventricular Catheter in Ventriculoperitoneal Shunt Surgery: Evaluation of Accuracy and Feasibility in a Prospective Cohort - Leu, Severina; Kamenova, Maria; Mariani, Luigi; Soleman, Jehuda (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Objective Ventriculoperitoneal shunt (VPS) placement is one of the most frequent neurosurgical procedures. The position of the proximal catheter is important for shunt survival. Shunt placement is done either without image guidance (“freehand”) according to anatomical landmarks or by use of various image-guided techniques. Studies evaluating ultrasound-guided (US-G) VPS placement are sparse. We evaluate the accuracy and feasibility of US-G VPS placement, and compare it to freehand VPS placement.Methods We prospectively collected data of consecutive patients undergoing US-G VPS placement. Thereafter, the US cohort was compared with a cohort of patients in whom VPS was inserted using the freehand technique (freehand cohort). Primary outcome was accuracy of catheter positioning, and secondary outcomes were postoperative improvement in Evans' index (EI), rates of shunt dysfunction and revision surgery, perioperative complications, as well as operation, and anesthesia times.Results We included 15 patients undergoing US-G VPS insertion. Rates of optimally placed shunts were higher in the US cohort (67 vs. 49%, p = 0.28), whereas there were no malpositioned VPS (0%) in the US cohort, compared with 10 (5.8%) in the freehand cohort (p = 0.422). None of the factors in the univariate analysis showed significant association with nonoptimal (NOC) VPS placement in the US cohort. The mean EI improvement was significantly better in the US cohort than in the freehand cohort (0.043 vs. 0.014, p = 0.035).Conclusion Based on our preliminary results, US-G VPS placement seems to be feasible, safe, and increases the rate of optimally placed catheters.
Keywords: ventriculoperitoneal shunt; image-guided neurosurgery; intraoperative ultrasound; hydrocephalus; surgical technique